Safety and efficacy indicators of guarana and Brazil nut extract carried in nanoparticles of coenzyme Q10: Evidence from human blood cells and red earthworm experimental model - Azzolin, Vitória Farina; Azzolin, Verônica Farina; da Silva Maia, Railla; Mastella, Moises Henrique [UNESP]; Sasso, Juliane Santiago; Barbisan, Fernanda; Bitencourt, Gustavo Rossato; de Azevedo Mello, Paola; Ribeiro, Ednea Maia Aguiar; Ribeiro, Euler Esteves; Nunomura, Rita de Cassia Saraiva; Manica da Cruz, Ivana Beatrice (Elsevier, 2024)
This study characterized a nanosupplement based on coenzyme Q10 containing guarana (Paullinia cupana) and Brazil nuts oil (Bertholetia excelsa) (G-Nut). Determined cytotoxic and oxi-immunomodulatory effects on human peripheral blood mononuclear cells (PBMCs) and its effect on mortality of red Californian earthworms (Eisenia fetida) and on the immune efficiency of its coelomocytes immune by in vitro exposure to yeast dead microorganism. The cytotoxic and immunomodulatory effects of G-Nut and the GN-Free extract (0.25–3 mg/mL) were determined in PBMC cultures. Apoptotic, oxidative, and inflammatory markers were determined using biochemical, immunological, and molecular protocols. The effects of G-Nut and GN-Free extracts on mortality and immune efficiency were investigated in earthworms. G-Nut and GN-Free did not induce cytotoxic events in PBMCs, triggering the decrease in apoptotic (caspases 3 and 8) gene expression, lipid and protein oxidation levels, or pro-inflammatory cytokine levels. G-Nut and GN-Free did not trigger earthworm mortality and improved coelomocyte immune efficiency by increasing Eisenia neutrophil extracellular DNA traps and brown body formation when exposed to dead yeasts. The G-Nut nanoformulation is safe and can be used as a new form of food supplement by oral or transdermal delivery.
Keywords: Bertholletia excelsa; Coenzyme Q10; Nanoparticle; Oxy-inflammatory; Paullinia cupana